Genetically Predicted Obesity Causally Increased the Risk of Hypertension Disorders in Pregnancy - Wang, Wenting; Tan, Jiang-Shan; Hua, Lu; Zhu, Shengsong; Lin, Hongyun; Wu, Yan; Liu, Jinping (Frontiers in Cardiovascular Medicine, 2022)
Aims: This study aims to evaluate the causal association between obesity and hypertension disorders in pregnancy. Methods: Two-sample Mendelian randomization (MR) study was conducted based on the data obtained from the GIANT (n= 98,697 participants) consortium and FinnGen (n= 96,449 participants) to determine the causal effect of obesity on the risk of hypertension disorders in pregnancy. Our primary genetic instrument comprised 14 single-nucleotide polymorphisms (SNPs) associated with obesity-related databases based on a genome-wide significance. The random-effects inverse-variance weighted (IVW) method was adopted as the main analysis with a supplemented analysis of the MR-Egger and weighted median approaches. Results: We found that all three MR methods showed that genetically predicted obesity causally increased the risk of hypertension disorders in pregnancy. IVW analysis provided obesity as a risk factor for hypertension disorders in pregnancy with an odds ratio (OR) of 1.39 [95% confidence interval (CI) 1.21–1.59; P = 2.46×10-6]. Weighted median and MR Egger regression also showed directionally similar results [weighted median OR=1.49 (95% CI, 1.24–1.79], P = 2.45×10-5; MR-Egger OR=1.95 (95% CI, 1.35–2.82), P = 3.84×10-3]. No directional pleiotropic effects were found between obesity and hypertension disorders in pregnancy with both MR-Egger intercepts and funnel plots. Conclusions: Our findings provide evidence of a significant causal association between obesity and hypertension disorders in pregnancy. Taking measures to reduce the proportion of obesity may help reduce the incidence of hypertension disorders in pregnancy.